2012
DOI: 10.1111/j.1551-2916.2012.05205.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Sintering of Nanocrystalline Zinc Oxide: Effect of Heating Rate Achieved by Field Assisted Sintering/Spark Plasma Sintering

Abstract: Using Field Assisted Sintering Technique/Spark Plasma Sintering the effect of heating rate on the sintering of zinc oxide at a temperature of 400°C has been investigated. For the highest heating rate of 100°C/min, relative density larger than 95% was achieved whereas at low heating rates only little shrinkage occurred. Hardness measurements, Transmission Electron Microscopy, and impedance spectroscopy revealed clear differences between heating rates. It was found that residual water is responsible for this beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 46 publications
0
25
0
2
Order By: Relevance
“…However, no faceting or abnormal grain growth is observed for NG20 sintered under dry conditions. In contrast, a raised fraction of faceted grain boundaries was recently observed for sintering of nanocrystalline ZnO in presence of water [60], which is discussed in context of occurrence of abnormal grain growth [61,62]. The formation of faceting is probably due to enhancement of surface diffusion by increased water vapor pressure.…”
Section: Effect Of Surface Bound Water On Development Of Morphologicamentioning
confidence: 91%
“…However, no faceting or abnormal grain growth is observed for NG20 sintered under dry conditions. In contrast, a raised fraction of faceted grain boundaries was recently observed for sintering of nanocrystalline ZnO in presence of water [60], which is discussed in context of occurrence of abnormal grain growth [61,62]. The formation of faceting is probably due to enhancement of surface diffusion by increased water vapor pressure.…”
Section: Effect Of Surface Bound Water On Development Of Morphologicamentioning
confidence: 91%
“…In general, the reduction in surface energy of the particles resulting from the adsorption of specific species of gas, water, or organics should be considered, [77] because this modifies the thermodynamical driving force to surface reduction and sintering. Schwarz et al [49] observed not only an increased densification rate for nanocrystalline zinc oxide with moisture in FAST/SPS but also a remarkable difference in final density at a lowered sintering temperature. The presence of water vapor in the sintering atmosphere is known to enhance surface diffusion of magnesia doped alumina, [65] titania, [78] magnesia, [79][80][81][82] or zinc oxide [64] due to chemical interaction of water with the surface of the oxide and surface diffusion of hydroxyl ions and protons.…”
Section: Role Of Atmospherementioning
confidence: 99%
“…[48] But in some cases (and possibly due to adsorbed water) higher heating rate can lead to higher final density, as shown for nanocrystalline zinc oxide and hydroxyapatite. [49,50] The fast densification by FAST/SPS can also reduce the interaction between the sintering material and graphite tool. An example is the full densification of boron suboxide (B 6 O) showing very high-hardness values of up to 45 GPa achieved in graphite dies by FAST/SPS whereas the synthesis in HP requires expensive hexagonal BN dies.…”
Section: Thermal Effectsmentioning
confidence: 99%
“…In general, there are two possibilities for how mass transport is taking part towards consequent reduction of pore volume under compaction without the necessary activation temperature for sintering. The lowest sintering temperature found for sintering of ZnO is reported to be 0.2 × T m at an external pressure of 50 MPa [37], i.e. 400 °C, which is well above the temperature found in the environmental chamber.…”
Section: Resultsmentioning
confidence: 97%